Fragment Compression through Distal Locking Hole by Screw with Washer: A Supplement to Nailing in Distal Tibia Fractures - Sunil G Kulkarni; Prashant B Dhamoji; Utkarsh K Vishwakarma; Madhura S Kulkarni; Sanghsen S Sawant; Nitin P Prajapat (Journal of Foot and Ankle Surgery (Asia Pacific))
Introduction: Distal tibial metadiaphyseal fractures are challenging fractures that need multiple principles of fixation for optimal stability. Conventionally, when the distal locking screw hole of tibia interlock nail coincides with the fracture site, either the screw hole is left empty or the inserted screw through the fracture site does not have a good hold of the screw. We propose the use of screw with washer for compression of fracture fragments through the distal locking screw hole of tibia interlock nail in specific distal tibia fractures. Materials and methods: Fifty patients with distal third tibia fractures were treated with interlock nail with use of screw with washer for compression of fracture fragments at distal locking screw holes. Distal tibia fractures with medial spike or comminution overlapping distal locking screw holes needed compression to align them and prevent any malangulation at the fracture site. There were 13 (43A1) type fractures, 18 (43A2) type fractures, and 19 (43A3) type fractures. Fibula fixation was done in 22 patients. Poller screw fixation was done in 28 patients. Functional outcome was assessed based on the Johner and Wruhs radiological and clinical criteria. Results: Forty-eight patients had excellent to good scores; 2 patients had fair score based on Johner and Wruhs radiological and clinical criteria. Conclusion: Screws inserted with washers generate significantly more compressive forces than screws inserted without washers. A screw with washer is an effective tool during fracture fixation to optimize compression, minimize the risk of intrusion of the screw head during insertion through the fracture site and avoid leaving empty distal locking screw holes at fracture site, which is prone to implant failure (nail breakage).